Time out of general surgery specialty training in the UK: a national database study - Elsey, Elizabeth J.; West, Joe; Griffiths, Gareth; Humes, David J. (Elsevier, 2018)
Objective:General surgery specialty training in the UK takes 6 years and allows trainees to take time out of training. Studies from the USA have highlighted an increasing trend for taking time out of surgical training for research. This study aimed to evaluate trends in time out of training and the impact on the duration of UK general surgical specialty training. Design, setting and participants: A cohort study using routinely collected surgical training data from the Intercollegiate Surgical Curriculum Programme (ISCP) database for General Surgery trainees registered from 1st August 2007. Trainees were classified as Completed Training or In-Training. Out of training periods were identified and time in training calculated (both unadjusted and adjusted for out of training periods) with a predicted time in training for those In-Training. Results: Of the trainees still In-Training (n=994), a greater proportion had taken time out of training compared with those who had completed training (n=360) (54.5% vs 45.9%, p<0.01). A greater proportion of the In-Training group had undertaken a formal research period compared to the Completed Training group (35.1% vs 6.1%, p<0.01). Total unadjusted training time in the Completed Training group was a median 6.0 (IQR 6.0- 7.0) years compared with a predicted unadjusted training time in the In-Training group, with an out of training period recorded, of a median 8.0 (IQR 7.0- 9.0) years. Conclusions: Trainees are increasingly taking time out of surgical training, particularly for research, with a subsequent increase in total time of training. This should be considered when redesigning surgical training programmes and planning the future surgical workforce.